Determination of Xylenol Orange Based on Chemical Oscillating Reaction Catalyzed by a Macrocyclic Complex - Hu, Lin; He, Jihui; Hu, Gang (Asian Journal of Chemistry, 2012)
A new analytical method for the determination of xylenol orange based on the oscillating system is proposed. The oscillating system involves a macrocyclic complex [CuL](ClO4)2 as catalyst, malic acid as organic substrate and sodium bromate as oxidant. The ligand L in the complex is 5,7,7,12,14,14-hexamethyl-1,4,8,11-tetraazacyclotetradeca-4,11-diene. The experimental results show that, when the system is perturbed by adding variable amounts of xylenol orange, the change of the oscillation amplitude is linearly proportional to the concentration of logarithm of the xylenol orange in the range 2.5 × 10-7-2.5 × 10-4 M. Hence, an array of xylenol orange involving its perturbation effects on a Belousov-Zhabotinsky system has been established.